Correlation between ecosystem service value and ecological risk in Chengdu - Geng Yongju; Zhou Guoqing; Wang Weiyi; Cai Yufu; He Taiyuan; Li Cong (E3S Web of Conferences, 2025)
This paper analyzes the changes in land use and landscape pattern index in Chengdu from 2000 to 2020 using the land utilization dataset of this period. The bivariate Moran’s I model, which can effectively explore the spatial interdependence between two variables, is employed. By using this model, we can more accurately analyze the spatial relationship between the value of ecosystem services and the ecological vulnerability levels at the individual grid - cell level in Chengdu. This helps to clarify the spatiotemporal pattern and relationship of watershed ecosystem service value and ecological risk. The research findings show that from 2000 to 2020, the land use in Chengdu changed continuously. The areas of cultivated land and grassland decreased significantly, while artificial surfaces expanded dramatically. The landscape fragmentation in Chengdu increased overall during this period. Notably, the ecological risk levels in Chengdu generally shifted from high and relatively low to low and moderate levels, indicating the positive impact of urban planning on the ecological environment. More importantly, the Local Indicators of Spatial Association (LISA) analysis reveals an inverse correlation between the per - unit - area ecosystem service value and the ecological risk index in different regions of Chengdu. This finding emphasizes the importance of enhancing ecological construction during urban development to ensure sustainable growth.